Harnessing Offshore Wind for Sustainable Economic Growth in Nordic Countries: Legal Innovations, Economic Opportunities, SDG and Policy Integration - Butt, Junaid; Kousar, Farzana (Acta Universitatis Danubius. Œconomica, 2024)
Offshore wind energy refers to the generation of electricity from wind turbines installed in bodies of water, typically seas or oceans. Sustainable economic growth refers to a mode of economic development that aims to meet the needs of the present without compromising the ability of future generations to meet their own needs. This research investigates the potential of offshore wind energy to drive sustainable economic growth in the Nordic countries. Framed within the context of the UN Sustainable Development Goals (SDGs), particularly SDG 7 on Affordable and Clean Energy, the study explores the interplay between renewable energy development and economic prosperity. The research examines innovative legal measures that can facilitate the development of the offshore wind industry in the Nordic region. This includes analyzing streamlining permitting processes, fostering public-private partnerships, and establishing frameworks for grid integration. By investigating the nexus of legal innovations, economic opportunities, and policy integration, this study aims to provide insights into how the renewable energy sector, particularly offshore wind, can contribute to achieving Sustainable Development Goals (SDGs) while fostering economic prosperity. Finally, the research emphasizes the importance of policy integration for maximizing the benefits of offshore wind development. It analyzes how national and regional policies can be harmonized to create a supportive environment for the industry. This includes considering environmental regulations, spatial planning, and social impact assessments. Through a multidisciplinary approach, this research examines the economic and legal measures necessary to optimize the benefits of offshore wind projects, including job creation, investment attraction, and regional development. By analyzing successful case studies and policy frameworks, this study seeks to offer actionable recommendations for policymakers, industry stakeholders, and researchers to navigate the complex landscape of offshore wind development and ensure its alignment with sustainable economic objectives in the Nordic region.